Paraneoplastic Autoimmunity Associated with Testicular Myeloid Sarcoma and Chronic Myelomonocytic Leukemia - Jeffrey W. Craig; Richard J. Lin (Case Reports in Hematology)
Myeloid sarcomas are rare extramedullary solid tumors composed of immature myeloid cells. The clinical presentations of these malignant neoplasms are highly variable, ranging from asymptomatic to localized mass effect. Here, we report an unusual case of myeloid sarcoma of the testis found in association with chronic myelomonocytic leukemia where the presenting symptoms were autoimmune pericarditis and migratory arthralgias and myalgias that preceded testicular enlargement by nearly three months. Treatment with both radical orchiectomy and leukemia-directed chemotherapy led to immediate reductions in symptom severity, suggesting that these early symptoms were paraneoplastic in origin. Review of the literature identified the association between hematological malignancies, including chronic myelomonocytic leukemia, and paraneoplastic autoimmune phenomena with features similar to polymyalgia rheumatica and rheumatoid arthritis. Importantly, rheumatologic symptoms related to these disease entities may be easily dismissed as vague or unrelated complaints or treated as purely rheumatologic conditions, thus delaying the formal diagnoses. Clinicians must recognize the common association between possible paraneoplastic rheumatologic symptoms and hematologic malignancies such as chronic myelomonocytic leukemia.